Caracterização de farinhas de sorgo (Sorghum bicolor) processadas em moinhos de milho e trigo : II — Qualidade protéica - Pinheiro Euclydes, Marilene; Gonçalves Junqueira, Roberta; Maffia, Lúcia Maria; Kalagi Kibuuka, Godfrey (Revista Ceres, 2025)
The purpose of this study was to obtain, through processing, a sorghum flour of good nutritional quality.